The structural basis for the phospholipid remodeling by lysophosphatidylcholine acyltransferase 3 - Qing Zhang (Nature Portfolio, 2021)
During phosphatidylcholine (PC) remodeling re-acylation is catalyzed by lysophosphatidylcholine acyltransferases (LPCAT). Here, the authors present crystal and cryo-EM structures of chicken LPCAT3 in the apo-, acyl donor-bound and acyl receptor-bound states, and based on the structures and further functional analysis they discuss the mechanism of the enzyme.